Implementing Gestalt Theory in UI/UX Design of Mobile Apps for Food Waste Reduction - Oktavia Oktavia; Silma Sundari; Feri Alpiyasin (LPPM STMIK Mardira Indonesia, 2025)
Participants in the Independent Study MSIB Batch 5's #Tech4Impact Skilvul Program are encouraged to create digital solutions for social problems, such as reducing food waste. A website-based e-commerce design was one of the first innovations to receive a 90 on the System Usability Scale (SUS). Two drawbacks were identified during evaluations: the incentive elements lack clear visual cues, and the design is not yet responsive on mobile platforms. Given the mobile-first trend and the critical role mobile applications play in delivering integrated, tailored, and practical transaction experiences, this poses a problem. The UI/UX design of the SaveBite mobile application is developed in this study by applying Gestalt Theory and Design Thinking. Gestalt principles improve consistency, visual perception, and interface navigation, while Design Thinking guarantees that the design is focused on user needs. The development is concentrated on making the reward elements more user-friendly and enhancing the mobile experience. With an average SEQ of 6.7 (or 95.7% ease of use) and a SUS score of 81.0, usability testing findings demonstrate a significant improvement over the prior website design. These results show that the prototype provides a reasonable degree of responsiveness, clarity, and comfort. This study shows the potential for increased user adoption while helping create mobile-based digital solutions to food waste problems. In the future, this application might be fully developed for community use, leveraging digital technology to reduce food waste sustainably.